Cardiovascular function shows early impairment in asymptomatic adolescents diagnosed with type 1 diabetes mellitus: an ultrasound-derived myocardial work study - Martina Ghirardo; Martina Ghirardo; Irene Cattapan; Irene Cattapan; Jolanda Sabatino; Jolanda Sabatino; Alice Pozza; Alice Pozza; Jennifer Fumanelli; Jennifer Fumanelli; Martina Avesani; Joaquin Gutierrez De Rubalcava Doblas; et al. (Frontiers in Cardiovascular Medicine)
BackgroundCardiac dysfunction and endothelial damage are known complications of type 1 diabetes mellitus (T1D) mainly affecting adults. However, some studies have shown that subclinical myocardial impairment already present during adolescence. Myocardial work (MW) has emerged as an afterload-independent tool that allows early identification of subclinical damage. This study aims to provide a comprehensive non-invasive cardiovascular evaluation of T1D adolescents using both conventional and advanced echocardiography.MethodsWe enrolled 31 patients, aged between 13 and 19 years, who were diagnosed with T1D for at least 10 years and were followed up by the Paediatric Diabetology Unit of our institution. We collected data relating to anthropometry, lifestyle, blood tests, glycemic control parameters, and conventional and advanced echocardiographic measurements. A comparison of MW parameters with the data from 31 age- and sex-matched healthy volunteers from a previous study in our lab was carried out.ResultsIn our population, the glycemic control parameters showed suboptimal control. While diastolic parameters were in the normal range for all the patients, E′ velocities and left atrial diameter were significantly worse in patients with poorer glycemic controls. Global longitudinal strain (GLS), global work index (GWI), and global work efficiency (GWE) were significantly lower in the T1D population compared to those in the healthy population (p < 0.001), while global wasted work was significantly higher in the T1D population (p < 0.001). Patients with stage 1 hypertension or a pre-hypertensive state exhibited pathological pulse wave velocities with values exceeding 8 m/s (>99th percentile).ConclusionsTo the best of our knowledge, this was the first study to investigate MW in T1D adolescents. The descriptive parameters of GLS and MW showed subclinical cardiac damage already during this timeframe. Therefore, these tools should be integrated into the cardiovascular assessment of diabetic adolescents, and preventive strategies should be implemented to maximize glycemic and pressure control effectiveness.